2016
DOI: 10.1051/matecconf/20178703010
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of colour, TSS and COD from palm oil mill effluent (POME) using acid-washed coconut shell activated carbon: Kinetic and mechanism studies

Abstract: Abstract. The disposal of palm oil mill effluent (POME) without proper treatment before being discharged into natural water sources has become undesirable because of high concentration of suspended solid (SS), oil and grease (O&G), chemical oxygen demand (COD) and biological oxygen demand (BOD). This study investigated the feasibility of removing colour, total suspended solid (TSS) and COD using acid-washed coconut shell based activated carbon (CSAC) through the evaluation of the adsorption uptake as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…This showed that the adsorption took place on a heterogeneous surface, rather than the homogenous surface (Mohammed, 2013). Similar result was obtained by Sia et al (2017) who revealed that the POME colour adsorption mechanism was mainly due to heterogenous system and chemical sorption. The adsorption rate was affected more by the number of available adsorption sites on the adsorbent surface than the effect of POME solution concentration.…”
Section: Adsorptionsupporting
confidence: 87%
See 3 more Smart Citations
“…This showed that the adsorption took place on a heterogeneous surface, rather than the homogenous surface (Mohammed, 2013). Similar result was obtained by Sia et al (2017) who revealed that the POME colour adsorption mechanism was mainly due to heterogenous system and chemical sorption. The adsorption rate was affected more by the number of available adsorption sites on the adsorbent surface than the effect of POME solution concentration.…”
Section: Adsorptionsupporting
confidence: 87%
“…Furthermore, this membrane showed very minimal signs of fouling and able to operate until five continuous cycles. Similar study was carried out by Tan et al (2017) who applied the same type of UF membrane but the incorporation of metal oxide was different. In this study, PVDF UF membrane incorporated with coupled zinc-iron oxide (ZIO) nanoparticles and was fabricated via similar phase inversion process.…”
Section: Membrane Technologymentioning
confidence: 64%
See 2 more Smart Citations
“…Recently, many different technologies have been utilized for removal of hazardous pollutants from water and wastewater, including biochemical methods [3], membrane separation [4], ion-echange [5], ultrafiltration [6], photocatalysis [7], coagulation/flocculation [8], and adsorption [9]. Among the mentioned methods, adsorption has some advantage when compared aforementioned conventional methods in terms the simplicity of utilization, effectiveness, low cost, no sludge formation, etc.…”
Section: Introductionmentioning
confidence: 99%